2023
DOI: 10.1021/acs.jced.3c00323
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Relative Static Permittivity: a Group Contribution Method Based on Perturbation Theory

Lisa Rueben,
Johannes Schilling,
Philipp Rehner
et al.

Abstract: The computer-aided design of (bio)chemical processes requires models that predict thermodynamic properties with as little experimental effort as possible. For the important class of electrolyte systems, the relative static permittivity of the solvent is an important thermodynamic property that depends on the temperature, pressure, composition, and molecular structure of the solvent. This work presents a broadly applicable model for the temperature-dependent relative static permittivity of pure and mixed solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Given the univariate dependence of the relative permittivity on dipole strength, it comes as little surprise that the perturbation theory by Tani et al and the model by Neumaier et al , showed great success in predicting the relative permittivities of the mixtures. However, both approaches rely on pure-component permittivity data; the Padé approximant for the correlation integral in the theory by Tani et al was fitted to numerical data, while the model by Neumaier et al requires some data on pure-component permittivities to fit the two adjustable parameters.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the univariate dependence of the relative permittivity on dipole strength, it comes as little surprise that the perturbation theory by Tani et al and the model by Neumaier et al , showed great success in predicting the relative permittivities of the mixtures. However, both approaches rely on pure-component permittivity data; the Padé approximant for the correlation integral in the theory by Tani et al was fitted to numerical data, while the model by Neumaier et al requires some data on pure-component permittivities to fit the two adjustable parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Neumaier et al modeled the correlation integral as I ( y ) = I d d normalΔ 9 17 π 2 = 1 + a 2 ( e y 1 ) where the so-called scaled dipole strength y = a 1 y is introduced. , The model has two adjustable pure-component parameters: the parameter a 1 in eq is meant to account for the nonsphericity of real fluids and must be equal to or greater than zero; the parameter a 2 scales the dependence of the correlation integral on the dipole strength. In this work, we individually adjusted the pure-component parameters to reproduce previously published data , for the relative permittivity of the three pure ST fluids with the reduced dipole moments μ* = 1, 1.5, and 2.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations